Young People - The Creators of New Uzbekistan (The Peerian Journal, 2023)
The article analyzes the socio-philosophical essence, social significance and influence of the reforms being carried out in Uzbekistan and the period of fundamental turning in the life of society, and the impact on the spiritual maturity of a person, and the issues related to the increasing need for factors to bring Uzbekistan to a new level are scientifically discussed